A Prospective Study of Frailty, Mortality and Required Level of Care in Elderly Requiring Support - Miki FUKUMA; Kuninori SHIWAKU (Shimane Journal of Medical Science, 2014)
This study aimed to identify the risk factors related to insurance care diversion by elucidating how frailty is related to mortality and required level of care in the elderly. We conducted a baseline survey of disease, lifestyle and frailty. The analysis subjects were 60 elderly requiring support (the support level group) and 62 independent elderly (the independent group). We then conducted a 4 year followup survey. Results showed that death in the support level group was significantly correlated with age >- 75 years, falls, male and physical exercise. In the independent group, death was significantly correlated with smoking and gait difficulty. Deterioration in required level of care in the support level group was significantly correlated with male and malnutrition. Death and deterioration were independent of disease and lifestyle and were associated with the frailty indicators falls, gait difficulty, and malnutrition for the required level of care in the individuals of the support level group. These results show that the need for preventive care services to focus on frailty prevention.